(untitled) (International journal of artificial intelligence, 2025)
This article explores the concept of emotive texts and the ways emotive dominance is expressed in both source and translated versions. It examines how emotional meaning is conveyed through linguistic and paralinguistic means, including interjections and related units, in correlating languages. The study discusses the role of emotiveness as a central communicative feature of the text, as well as the challenges translators face when rendering ethnospecific emotional and cultural codes. Special attention is given to the author’s subjectivity in the original text and its influence on the choice of linguistic means in translation. The paper also highlights the impact of textual structure, punctuation, and narrative dynamics on the perception and interpretation of emotive texts by readers and translators.